2023
DOI: 10.1111/ijd.16859
|View full text |Cite
|
Sign up to set email alerts
|

Acquired dermal macular hyperpigmentation: an overview of the recent updates

Shikha Shah,
Narayanan Baskaran,
Keshavamurthy Vinay
et al.

Abstract: Acquired dermal macular hyperpigmentation (ADMH), previously known as macular pigmentation of uncertain etiology (MPUE), is an umbrella concept that unifies the distinct but overlapping acquired dermal pigmentary disorders like lichen planus pigmentosus, ashy dermatosis, erythema dyschromicum perstans, Riehl’s melanosis and pigmented contact dermatitis. All of these disorders usually lack a clinically apparent inflammatory phase, are characterised by dermal pigmentation clinically and histologically, and have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…A population-based survey in France revealed that tattooing was associated with lower quality of life scores, particularly among individuals with multiple tattoos [11]. Psychological disturbances, including anxiety and depression, may ensue, thus emphasizing the need for future research for more effective therapy [12].…”
Section: Effects On Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…A population-based survey in France revealed that tattooing was associated with lower quality of life scores, particularly among individuals with multiple tattoos [11]. Psychological disturbances, including anxiety and depression, may ensue, thus emphasizing the need for future research for more effective therapy [12].…”
Section: Effects On Quality Of Lifementioning
confidence: 99%
“…Incorporating extended follow-up durations would help draw meaningful conclusions since the reduction in dermal pigmentation is slow, with a potential for relapse. For conditions like ADMH that have a variable and unpredictable course with a potential for spontaneous resolution, it would be helpful to include a control group to evaluate whether the observed improvement may be ascribed to the treatment method [12]. The use of the 1064 nm ps-laser in ADMH is yet to be explored; additional research is needed to characterize this condition and establish consistently effective treatments [32].…”
Section: Literature Gap and Future Directionsmentioning
confidence: 99%